Abstract ID: 171 A Monte Carlo study to reduce range uncertainty in proton beam therapy via prompt gamma-ray detection. (January 2018) - Panaino, C.; Taylor, M.J.; MacKay, R.; Merchant, M.J.; Price, T.; Pheonix, B.; Green, S.
Abstract : In proton beam therapy precise knowledge of the proton beam range is essential to guarantee the treatment's efficacy and to avoid unnecessary toxicities. Unlike photon beams, protons stop inside the patient's body, therefore a direct detection of the distal fall-off is impossible. One technique to determine the beam range is to detect the prompt gamma (PG) rays emitted from the nuclei de-exciting following proton bombardment[1] . PG emission is almost instantaneous and has a high-production rate. The aim of this project is to develop a new method, based on an optimized PG detector system, which can achieve 3D range determination with an uncertainty of no more than 2 mm. The presented method is based on the detection of discrete gamma-rays. As a first step, the position reconstruction capability of the PG detector system was examined by means of Geant4 simulations. The prototype system is comprised of 12 LaBr3 (Ce) detectors. The information recorded by each individual detector is fed into a reconstruction algorithm to determine the gamma-ray emission point in 3 dimensions. The development of the algorithm, proof-of-principle and simulation validation, have all been conducted using a sealed 60 Co source. Our simulations demonstrate that an ideal detector system with the current reconstruction algorithm is capable of determining the source position with sub-millimetre accuracy. Having obtained proof-of-principle for the reconstruction algorithm the next stage is to investigate how implementing a realistic detector system affects the reconstruction performance. In addition, the ability of the detector system to discriminate between multiple sources in different positions is under evaluation.